Implementasi Website untuk Mendukung Informasi dan Pemasaran Produk UMKM Tenun Desa Sukarare - Fahrozi, Lalu Harly; Priyanto, Dadang (Indo-MathEdu Intellectuals Journal, 2026)
MSMEs (Micro, Small, and Medium Enterprises) play an important role in the Indonesian economy, including in Sukarare Village, Central Lombok, which is famous for producing traditional woven fabrics of the Sasak Tribe. Marketing processes in this village are still conventional, so market reach is limited. This study aims to implement a website as a medium for information and marketing of woven products to increase presence in the digital market while preserving local culture. The method used is the waterfall system development, which includes needs analysis, design, creation, and testing. Data was collected through observation, interviews with MSME actors, and literature studies. The research resulted in a PHP and MySQL-based website with features for UMKM profiles, product catalogs, order contact, and activity documentation. Alpha testing showed that all features function as expected for both owners and customers. This website is effective as a means of information and digital marketing for Tenun Sukarare UMKM and can be used as a web-based sales transaction information system for woven fabrics.